The Experience of Breast Reconstructive Microsurgery - Bayu Brahma; Samuel J Haryono (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2016)
Autologous techniques in oncoplastic breast surgery may result in graft donor site morbidity. Microsurgery has become a new surgical modality for breast reconstruction; it is a less invasive procedure. In recent experience, we have applied microsurgical technique in oncoplastic breast procedures to minimize morbidity.We reviewed the charts of breast cancer/tumor patients with microsurgical reconstruction.From February 2013 to July 2016, we performed 36 perforator flaps for breast reconstruction. The mean age of the patients was 44.4±6.7 years old, with the median tumor size of 3.7 (1.5-20) cm. No special type of carcinoma (NST) was accounted in 25 (69.4%) cases. Oncoplastic breast conserving surgery (OPS) was the procedure of choice in 17 (47.2%) cases and mastectomy was followed by free flap in 19 (52.8%) patients. In OPS, we used various perforator flaps to cover the defect. Thoracodorsal artery perforator flap (TDAP) was the most common technique used in 8 (22.2%) cases, then lateral intercostal artery (LICAP) flap in 6 (16.7%) cases, anterior intercostal artery (AICAP) flap in 1 (2.8%) cases, and superficial epigastric artery (SEAP) flap in 2 (5.6%) cases. Deep inferior artery perforator (DIEP) free flap was the reconstruction option after mastectomy. During follow-up with the mean time of 12.7±11.4 months, there were 1 local recurrence, 2 regional and systemic metastases, and 1 death due to cerebrovascular disease. There were no flap loss after pedicle perforator reconstruction but total flap necrosis occurred in 5 patients with DIEP free flap. In one patient, we successfully salvaged the flap that had venous congestion. There was no seroma at donor site and no limitation in abdominal wall function after DIEP reconstruction.In our experience, microsurgical reconstruction in breast surgery has been a safe procedure and has less donor site morbidity. Flap failure rate may be improved by refining microsurgical technique